2023
DOI: 10.3390/nu15041036
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Approaches to Modulate Cardiovascular Disease Risk in Systemic Lupus Erythematosus: A Literature Review

Abstract: Systemic lupus erythematosus (SLE) is a chronic pathology characterized by a bimodal mortality pattern attributed to clinical disease activity and cardiovascular disease (CVD). A complex interaction between traditional CVD risk factors such as obesity, dyslipidemia, smoking, insulin resistance, metabolic syndrome, and hypertension, as well as the presence of non-traditional CVD risk factors such as hyperhomocysteinemia, pro-inflammatory cytokines, and C-reactive protein levels, has been suggested as a cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…Common food sources of methyl donor nutrients including green vegetables, eggs, red meat, milk, cheese, and yogurts should be included daily in the diet of patients with SLE. Also, taking account of the lack of clinical trials on methyl donor dietary supplementation in SLE, nutrient intake according to recommendations should be encouraged [29].…”
Section: Future Perspectives On Precision Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common food sources of methyl donor nutrients including green vegetables, eggs, red meat, milk, cheese, and yogurts should be included daily in the diet of patients with SLE. Also, taking account of the lack of clinical trials on methyl donor dietary supplementation in SLE, nutrient intake according to recommendations should be encouraged [29].…”
Section: Future Perspectives On Precision Nutritionmentioning
confidence: 99%
“…In addition, a dietary pattern to prevent/control the increased risk of cardiovascular diseases may be beneficial for these patients [28]. Some nutrients with immunomodulatory and antioxidant capacity, as well as anti-cardiometabolic dietary patterns, could reduce SLE severity and organ damage [29]. Available literature has shown that a diet with high contents of fiber, mono/polyunsaturated fatty acids, vitamins, minerals (especially those with antioxidant activity), and polyphenols can modify disease activity by modulating the inflammation and immune functions of SLE [30].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Several therapeutic approaches have been proposed to prevent the development of hypovitaminosis D and CVD in SLE patients; some studies have suggested that diet represents a modifiable lifestyle risk factor that can significantly influence clinical disease activity and cardiometabolic outcomes by modulating inflammatory and immune responses in autoimmune diseases. 4,10 Previous studies have reported that SLE patients show malnutrition characterized by dietary intake deficiencies of immunomodulatory micronutrients such as vitamins A, C, and D. 11 Moreover, the study of dietary patterns (DPs) is a valid approximation of diet, considering food, nutrients, and other dietary components that reflect population eating habits. 12 In the general population, westernized DPs positively correlate with CVD risk; conversely, a higher diet quality that includes healthy foods, such as fruits, vegetables, whole grains, and unsaturated fats, has been associated with lower cardiometabolic risk factors and CVD.…”
Section: Introductionmentioning
confidence: 99%
“…SLE is one of the most prevalent extra-intestinal autoimmune diseases and is characterized by the unregulated production of autoantibodies and immunemediated tissue damage [4]. The cause of SLE is not fully understood, but genetic and environmental factors are thought to play a role [5][6][7].…”
Section: Introductionmentioning
confidence: 99%